MODEL PEMBERDAYAAN EKONOMI BERBASIS SAPI MAWAH UNTUK KETAHANAN PANGAN BERKELANJUTAN DI KOTA LHOKSEUMAWE : indonesia - Hasra, Lusi Dyana Hasra; Taqdirul Alim, Muhammad; Al Fahmi, M. Lutfi; Rahman, Bobby; Andirfa, Mulia (FISIP Universitas Malikussaleh, 2026)
This research is based on the low level of community welfare and food security in Lhokseumawe City, despite the area having great potential for beef cattle farming. Mawah cattle is one of the traditional livestock systems that still exist in the community, which is a profit-sharing cooperation pattern between livestock managers and capital owners. However, this system has not been systematically managed to date, lacks strong institutions, and has not been integrated with local economic empowerment programs. This study aims to develop and test a mawah cattle-based economic empowerment model that is structured, participatory, and appropriate to the socio-economic conditions of the Lhokseumawe City community. It is hoped that the results will improve the welfare of livestock farmers and support sustainable food security that relies on local resources. An associative quantitative method with a survey was conducted on one hundred mawah cattle farmers. To determine the relationship between farmer participation, economic welfare, and household food security, analytical techniques such as Pearson correlation and multiple regression were used. Before being used to collect data, the instrument was tested for validity and reliability.